ACCOUNTABILITY OF TAX RECEIVABLE MANAGEMENT: A CASE STUDY AT DIRECTORATE GENERAL OF TAXES - Asqolani, Asqolani; Andriana, Nina; Hadi, Miftahul; Fathoni, Nur (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2023)
The audit results of the Audit Board (BPK) on the management of tax receivables by the Directorate General of Taxes (DGT) found inadequacy in the administration of tax receivables with a value of more than Rp 20 trillion and repeated from previous years. The novelty of this study is the use of the Global Accountability Project (GAP) approach and OECD Principles of Corporate Governance to see the extent of public sector accountability in the management of tax receivables by DGT. This research uses qualitative methods using primary data, interviews with DGT, the Audit Board, and the Inspectorate General of the Ministry of Finance (ITJEN), and secondary data related to performance achievements during 2019-2022. The results show that, generally, accountability for tax receivables management by DGT has accountability principles in GAP and OECD Principles of Corporate Governance. Still, several things need to be improved, such as improving the administration of overdue receivables, adding bailiffs, regulating tax penalties that have yet to be issued, cooperating with third parties, and increasing tax collection budgets.